Proceedings of the Conference on Principles, Systems and Applications of IP Telecommunications 2014
DOI: 10.1145/2670386.2670390
|View full text |Cite
|
Sign up to set email alerts
|

Network security through software defined networking

Abstract: Network security is a predominant topic both in academia and industry. Many methods and tools have been proposed but the attackers are still able to launch massive and effective attacks. Keeping the pace with the new threats appearing or becoming more sophisticated everyday is of a paramount of importance. Software Defined Networking (SDN) has recently emerged and promotes the programmability of the networks, which thus allows to enable in-network security functions. This includes firewalls, monitoring applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In this section we highlight relevant research work done in the domain of DDoS defense with SDN (other than [10], discussed in Section 1). This work can roughly be divided into DDoS defense mechanisms against the core SDN infrastructure and the approaches that leverage SDN against DDoS attacks [15].…”
Section: Related Workmentioning
confidence: 99%
“…In this section we highlight relevant research work done in the domain of DDoS defense with SDN (other than [10], discussed in Section 1). This work can roughly be divided into DDoS defense mechanisms against the core SDN infrastructure and the approaches that leverage SDN against DDoS attacks [15].…”
Section: Related Workmentioning
confidence: 99%
“…Complementarily, Scott et al [22] investigate possible new security issues introduced through SDN and identify the affected layers. Focusing on network security approaches using SDN capabilities, François et al [10] reviews recent research efforts and provides a qualitative comparison, complementary to our analytical and empirical evaluation. Furthermore, existing work has been focusing on more specific attacks and their mitigation.…”
Section: Related Workmentioning
confidence: 99%
“…Besides this Scott et al [16] investigated possible new security issues introduced through SDN and identified affected layers. François et al [11] reviewed SDN security approaches according to their scope, practicability and advantages.…”
Section: Related Workmentioning
confidence: 99%